Engaging research communities in writing studies : ethics, public policy, and research design - Phelps, Johanna L. (New York, NY : Routledge, 2021)
"This book invites readers to reconsider how writing studies researchers work with Institutional Review Boards (IRBs) on behalf of their communities and argues that engaging with IRBs during the research design process helps practitioners conduct research more quickly and effectively. Using empirical data from both writing studies and extra-disciplinary contexts, Dr. Johanna Phelps presents findings from two discipline-wide studies, as well as metadata from two IRBs, to develop a principled engagement framework for writing studies researchers to interact with their communities. Phelps further examines the many facets of conducting research with human participants-from comprehending federal policy updates to pondering specific ethical issues to developing detailed research designs-and explores the confluence of ethics, policy, and methodology in a thoroughgoing philosophical investigation of writing studies as a public good. This engaging and timely exploration of research design will be an important resource for scholars and students of writing studies; rhetoric and composition; technical and professional communication; cultural rhetoric; literacy studies; research design; research methodologies; research ethics; IRBs; justice; and critical theory. Chapter 4 and Interchapter 4 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license "--
Introduction -- First Interchapter: Defining and Historicizing Research with Human Participants -- Situating Justice in the Research Enterprise -- Second Interchapter: Surveys as a Data Collection Method in Writing Studies -- Metadata: What We Know About Research with Human Participants -- Third Interchapter: "Medium" Data, Interviewing, and Corpus Analysis -- All "Spun Up": Findings from Familiar and Unfamiliar Methods -- Fourth interchapter: Collecting and Working with Census Data -- Don't be too WEIRD: Research for the Future of Writing Studies -- Fifth interchapter: Revisions to the Common Rule -- Ethical Praxis at Sites of Writing Studies Research -- Sixth interchapter: Questions to Consider when Designing Justice-Driven Research -- Centering Practical Ethics in Writing Studies Research.
OCLC-licensed vendor bibliographic record.
Keywords: English language -- Rhetoric -- Study and teaching -- Research -- Methodolgy; Academic writing -- Study and teaching -- Research -- Methodology; Research -- Moral and ethical aspects; Institutional review boards; LANGUAGE ARTS & DISCIPLINES / Composition & Creative Writing; EDUCATION / Higher